Flohal Variations and Seed Viability in Tecomella Undulata (Sm.) Seem. In Indian Desert - prakash, B S.V; Sen, D N (Annals of Arid Zone, 2016)
Tecomella undulata (Sm.) Seem. (Bignoniaceae), a common tree in the desert region produces yellow. orange-red and red coloured flowers. Only the seeds formed from yellow flowers are viable. The trees with yellow flowers are dominant and have been considered as most advanced and appear to be more suitable for arid environment.